Mixed infections with Chlamydia and porcine epidemic diarrhea virus - a new in vitro model of chlamydial persistence - Kaiser Carmen; Schifferli Andrea; Ziegler Urs; Dumrese Claudia; Borel Nicole; Pospischil Andreas (BMC Microbiology, 2010)
Abstract Background Chlamydiae induce persistent infections, which have been associated with a wide range of chronic diseases in humans and animals. Mixed infections with Chlamydia and porcine epidemic diarrhea virus (PEDV) may result in generation of persistent chlamydial infections. To test this hypothesis, an in vitro model of dual infection with cell culture-adapted PEDV and Chlamydia abortus or Chlamydia pecorum in Vero cells was established. Results Infected cultures were investigated by immunofluorescence (IF), transmission electron microscopy (TEM) and re-infection experiments. By IF, Chlamydia-infected cells showed normal inclusions after 39 hpi. Dual infections with Chlamydia abortus revealed a heterogenous mix of inclusion types including small inclusions consisting of aberrant bodies (ABs), medium-sized inclusions consisting of ABs and reticulate bodies and normal inclusions. Only aberrant inclusions were observable in dual infection experiments with Chlamydia pecorum and PEDV. TEM examinations of mixed infections with Chlamydia abortus and Chlamydia pecorum revealed aberrant chlamydial inclusions containing reticulate-like, pleomorphic ABs, which were up to 2 μm in diameter. No re-differentiation into elementary bodies (EBs) was detected. In re-infection experiments, co-infected cells produced fewer EBs than monoinfected cells. Conclusions In the present study we confirm that PEDV co-infection alters the developmental cycle of member species of the family Chlamydiaceae, in a similar manner to other well-described persistence induction methods. Interestingly, this effect appears to be partially species-specific as Chlamydia pecorum appears more sensitive to PEDV co-infection than Chlamydia abortus, as evidenced by TEM and IF observations of a homogenous population of aberrant inclusions in PEDV - Chlamydia pecorum co-infections.